Hubungan Pola Makan, Tingkat Kecukupan Energi, dan Protein dengan Status Gizi pada Remaja - Harvita Damara Utami; Kamsiah Kamsiah; Afriyana Siregar (Jurnal Kesehatan, 2020)
Adolescence is a time of growth and development. The process of growth and development takes place quickly so that the level of adequate protein and energy increases. Diet is an important habit that can affect nutritional status and meet nutritional needs. The research objective was to determine the relationship between diet, energy, and protein adequacy levels with adolescent nutritional status. The research design used analytic observational with the cross sectional approach. The population of all respondents aged 12-16 years at SMP IT Iqra consisting of 491 people with 88 people as the sample, using stratification random sampling technique. Data collection used primary data with the FFQ form and Food Recall for nutritional status using scales and microtoise. Data processing is carried out in several steps, editing, coding, tabulating, entry, and cleaning. Data analysis was univariate and bivariate with the Chi-square test. The results showed that there was a relationship between diet, energy adequacy level, and protein adequacy level with adolescent nutritional status. In conclusion, there is a significant relationship between diet, energy adequacy level, and protein adequacy level with adolescent nutritional status. It is better if schools conduct education about good eating patterns and eating portions by the guidelines for balanced nutrition to the Teens of SMP IT Iqra Bengkulu City so that their normal nutritional status increases.